Cat bearing gifts ebook - Murphy, Shirley Rousseau (Joe Grey, 2023)
A car crash, stolen treasure, a dead thief, and a blonde divorcée have a feline P.I. and his four-legged cohorts clawing for justice in this cozy mystery. On the twisting road home from San Francisco, tortoiseshell Kit and her elderly housemates, Lucinda and Pedric Greenlaw, are hurt in a terrible car crash. The accident is terrifying enough, but then two dangerous men steal the Greenlaw's town car, making off with a hoard of jewels and gold carefully hidden in the car. As paramedics rush the Greenlaws to the emergency room, a badly shaken Kit hides from hungry coyotes, waiting for Joe and their human friends to rescue her. Back home in Molena Point, Joe Grey and his tabby lady prowl an abandoned stone cottage where they've discovered two rough-looking men hiding. Determined to help the Greenlaws, Kit follows the two housebreakers: one badly injured, the other eager to end his partner's misery in order to make off with more wealth than he realizes. But the cat's investigation is in trouble as they claw their way to the truth, hoping that tomcat Misto and his unfailing memory might provide some answers to their questions. Praise for Cat Bearing Gifts "Talking cat fans will welcome Murphy's exciting 18th mystery featuring feline Joe Grey. . . . Anyone unfamiliar with this cozy series will be quickly drawn in by the complete believability of Murphy's crime-solving felines and their helpful human companions." — Publishers Weekly